Does the combination of tramadol with methadone provide better analgesic effect than methadone alone, in dogs undergoing routine ovariectomy? - Vieira, Patrícia Isabel Pereira (2022)
This study aims to evaluate tramadol’s effect during elective ovariectomy in female dogs under general anaesthesia with isoflurane, premedicated with 0.025 mg/kg medetomidine IM, 0.2 mg/kg methadone IM and 2 mg/kg ketamine IM. Seventeen female dogs were divided into control (CG) and tramadol (TG) groups. Dogs in the TG also received a 4 mg/kg IV tramadol bolus one minute prior to skin incision. Heart rate (HR), systolic blood pressure, and mean blood pressure were recorded at baseline, skin incision, traction (T1) and clamping (T2) of the right ovarian pedicle, and traction and clamping of the left ovarian pedicle. Tramadol caused a 39.8% (p<0.05) and a 31.9% (p<0.05) HR increase at T1 and T2, respectively, when compared to the CG, which lasted a maximum of eight minutes. Although tramadol has a potential positive chronotropic effect, it can safely provide additional intraoperative analgesia before intense noxious stimuli, for at least seven minutes; SERÁ QUE A COMBINAÇÃO DO TRAMADOL COM A METADONA PROPORCIONA UM EFEITO ANALGÉSICO MELHOR DO QUE A METADONA SOZINHA, EM CADELAS SUJEITAS A OVARIECTOMIA DE ROTINA? RESUMO: Este estudo tem como objetivo avaliar o efeito do tramadol durante a ovariectomia eletiva de cadelas anestesiadas com isoflurano, pré-medicadas com 0.025 mg/kg de medetomidina IM, 0.2 mg/kg de metadona IM e 2 mg/kg de cetamina IM. Dezassete cadelas foram divididas em grupo de controlo (GC) e tramadol (GT). No GT receberam também um bólus IV de tramadol a 4 mg/kg, um minuto antes da incisão cutânea. A frequência cardíaca (FC), pressão arterial sistólica e pressão arterial média foram registadas na “baseline”, incisão cutânea, tração (T1) e pinçamento (T2) do pedículo ovárico direito, e tração e pinçamento do pedículo ovárico esquerdo. O tramadol causou um aumento de 39.8% (p<0.05) e 31.9% (p<0.05) da FC em T1 e T2, respetivamente, comparando com o GC, que durou no máximo oito minutos. Apesar do potencial efeito cronotrópico positivo do tramadol, este proporciona analgesia intraoperatória adicional, de forma segura, antes de estímulos nóxicos intensos.